1976
DOI: 10.1115/1.3423920
|View full text |Cite
|
Sign up to set email alerts
|

Optical Holography

Abstract: The authors make no attempt to summarize the results available in this area through approximate solutions of various kinds to the 3-D field equations. Nor do they present, for readers prepared to utilize modern computer techniques, finite element, boundary integral, and other numerical techniques for obtaining such solutions. Finally, it seems to the reviewer that there is little added to this book by an "Introductory Chapter" of approximately 40 pages, authored by Sih, on the "strain-energy-density factor" th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 0 publications
2
108
0
Order By: Relevance
“…Optical interferometry (Nakano et al 1997) and surface grating diffraction (Zuliani et al 1973) have demonstrated to be feasible methods for specular specimen surfaces, while two approaches based on the recording of holograms have succeeded in this challenge for surfaces of non-specular finish: holographic interferometry and TV holography. (Collier et al 1971) are based on the interferometric comparison of two or more optical wavefronts scattered from the specimen surface, each corresponding to a different mechanical state. This allows extracting the map of the optical phase-difference between successive states, which is proportional to a certain component of the surface displacement (usually the out-of-plane one).…”
Section: Whole-field Techniquesmentioning
confidence: 99%
“…Optical interferometry (Nakano et al 1997) and surface grating diffraction (Zuliani et al 1973) have demonstrated to be feasible methods for specular specimen surfaces, while two approaches based on the recording of holograms have succeeded in this challenge for surfaces of non-specular finish: holographic interferometry and TV holography. (Collier et al 1971) are based on the interferometric comparison of two or more optical wavefronts scattered from the specimen surface, each corresponding to a different mechanical state. This allows extracting the map of the optical phase-difference between successive states, which is proportional to a certain component of the surface displacement (usually the out-of-plane one).…”
Section: Whole-field Techniquesmentioning
confidence: 99%
“…Combining equation (7.2) and equation (7.3), and assuming a point source and detector pixels of negligible size, we obtain 4) where the period of the fringes in scattering angle a across the detector in the region of overlap is…”
Section: Beam Smaller Than Unit Cellmentioning
confidence: 99%
“…The beam may be focused to a point a small distance Df from the sample, measured along the optic axis, and we take a sample-to-detector distance L. Where the aperture is coherently filled (CCB) and the sample not periodic, this geometry has a rich history, because it corresponds to the case originally analysed in detail by Gabor for inline, divergent beam holography (see [4] for a review). Then, because it produces a point-projection real-space shadow image with magnification M ¼ L/Df ( potentially with nanometre resolution [5]), it solves the phase problem [6].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent advances in high resolution spatial sensors, such as charge-coupled devices ͑CCD͒, has prompted the reassessment, in the new context of digital holography, of several original ideas that had emerged from the seminal work of Gabor 3 and Leith. 4 Digital holography refers to holographic methods that use solid-state detectors ͑such as CCDs͒, and store the hologram in digital form.…”
Section: Guy Indebetouw A) and Prapong Klysubunmentioning
confidence: 99%